La construcción del consumo de energía limpia en las empresas del sector energético en el Perú, 2007-2021 - Chavez Barboza, Claudia Andrea (2024)
The energy transition for Peru is a process that keeps obtaining more interest in companies in the energy sector, as it is a necessity in the face of the drastic climate changes that affect the country, a faster evolution highly contributes to reduce greenhouse emissions that generate a negative impact on environmental sustainability and quality of life for living beings. This research considers that Legislative Decree No. 1002 published in 2008 with the objective of promoting investment for the generation of electricity with the use of renewable energies, and later with the objective agreed in the Paris Agreement, helped the government to keep the energy sector regulated and continue with the purpose of promoting investment in the production of electricity through the development of clean energies at companies in the energy sector. Likewise, this research aims to analyze and explain the evolutionary process from the perspective of the main electricity generating companies in Peru, Enel Generación, Kallpa Generación and Electroperú, in addition to analyzing the main limitations that slow down a rapid and efficient energy transition.